2021
DOI: 10.2298/zmspn2141069s
|View full text |Cite
|
Sign up to set email alerts
|

Determination of tropane alkaloids in corn puffs by the LC-MS/MS

Abstract: The interest in tropane alkaloids (TA) as food contaminants is increasing. A sensitive and selective LC-MS/MS method was applied for the analysis of corn puff samples from the Serbian market. Only atropine was quantified in 22% of the samples. In case of scopolamine, although not quantified, it was detected in 22% of the samples. Whether the acute reference dose (ARfD) could be exceeded was checked on a case-by-case basis for the individual products under assessment. Due to their low body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The study of the 18 corn puff samples showed that 22.2% of all the samples had atropine (1.03-1.58 μg/kg) and scopolamine (0.29-0.47 μg/kg) detections [15]. Out of the 12 tested popcorn samples in 41.7% atropine (from 5.3 to 28.0 μg/kg) and scopolamine (from 2.1 to 6.3 μg/kg) were detected.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The study of the 18 corn puff samples showed that 22.2% of all the samples had atropine (1.03-1.58 μg/kg) and scopolamine (0.29-0.47 μg/kg) detections [15]. Out of the 12 tested popcorn samples in 41.7% atropine (from 5.3 to 28.0 μg/kg) and scopolamine (from 2.1 to 6.3 μg/kg) were detected.…”
Section: Discussionmentioning
confidence: 99%
“…The ESI source was used with the following settings: drying gas (nitrogen) temperature of 200 • C, drying gas flow rate 16 L/min, nebulizer pressure 30 psi, sheath gas temperature of 300 • C, sheath gas flow 12 L/min, and capillary voltage 3000 V. The detection was performed using the dynamic multiple reactions monitoring mode (dMRM). The Agilent MassHunter software (v.B.10.0 SR1 Agilent Technologies, 2006-2019, Santa Clara, United States) was used for the optimization and quantification [15].…”
Section: Instrumentationmentioning
confidence: 99%
See 3 more Smart Citations